In the south slavonic garden - Marelj, Marijana (Linguistica (Ljubljana), 2016)
This paper deals with morphological, syntactic, semantic, and pragmatic aspects of the so-called Cognate Object Construction with particular reference to Serbo-Croatian and Slovene. The relevance of an examination of such morphologically robust languages is manifold. It facilitates an understanding of some of the puzzling properties of the construction cross-linguistically, offers a way of explaining the noted disagreement regarding judgments found in the literature on Germanic languages such as English and also presents a clear case where (contrary to the dominant view in the literature) morphology seems to deceive, rather than inform us, about syntax. Based on a barrage of tests, I argue that there are two types of cognate objects: arguments and non-arguments. Extending the treatment of modifiers within the Davidsonian tradition to the latter, I analyse them as first-order predicates. This allows me to capture their core properties, among which is the obligatory modification, something unaccounted for in the literature. The semantic parallelism between the adverbial modifiers and non-ACOs extends to the syntax as well. Treating non-ACOs as adjuncts solves the problem of the scarcity of syntactic space that arises with unaccusative verbs that license them. ACOs, on the other hand, behave syntactically and semantically like run-of-the-mill arguments and a run-of-the-mill transitive syntax can be maintained (for a majority of them) instead.
Keywords: complément d'objet interne; croate; Croatian; glagol; hrvaščina; južnoslovanski jeziki; langues slaves méridionales; morfologija; morphologie; objet; povedek; prédicat; predmet; semantics; semantika; sémantique; serbe; skladnja; Slovene; slovenščina; South Slavic languages; srbščina; syntax; syntaxe; tavtološki predmet; verb; verbe